Synergistic effect of quorum sensing genes in biofilm development and PAHs degradation by a marine bacterium. Issue 3 (8th April 2016) - Kumari, Supriya; Mangwani, Neelam; Das, Surajit
ABSTRACT: Quorum sensing (QS) is a prevalently found intercellular signaling system in bacteria. QS system bestows behavioral coordination ability in bacteria at high population density. QS via acylated homoserine lactone (AHL) is extensively conserved in Gram-negative bacteria and plays crucial role in regulating many biological processes. The role of QS genes coding for AHL synthase enzyme ( lasI  and  rhlI ) was established in bioremediation of polycyclic aromatic hydrocarbons (PAHs) viz. phenanthrene and pyrene. AHL producing biofilm forming marine bacterium Pseudomonas aeruginosa N6P6 was isolated by selective enrichment on PAHs. AHL production was confirmed using AHL bioreporters and GC-MS analysis. Biofilm development and its architecture was significantly (P < 0.05) affected by alterations in lasI / rhlI  expression. The lasI / rhlI  gene expression pattern significantly influences biofilm formation and subsequent degradation of PAHs. The integrated density of Pseudomonas aeruginosa N6P6 biofilm was highest for 48 h old biofilm and the PAHs (phenanthrene and pyrene) degradation was also found maximum (85.6 % and 47.56 %) with this biofilm. A significant positive correlation ( P < 0.05) was observed between lasI expression and PAHs degradation. The role of QS genes in biofilm formation and degradation of PAHs was validated by blocking the transcription of lasI/rhlI  by a QS inhibitor (QSI) tannic acid. Further, application of such QS positive isolates in PAHs contaminated sites could be a promising strategy to improve the PAHs bioremediation.